Diversidade em Modulação Aplicada a Canais de Comunicações MóveisDOI: 10.14209/jcis.2002.4 - Terllizzie A. Lopes, Waslon; F. Galdino, Juraci; S. Alencar, Marcelo (Journal of Communication and Information Systems, 2015)
The performance of mobile communications systems can be significantly improved by using the modulation diversity technique which is, basically, based on the combination of a suitable choice of the reference angle of an MPSK constellation with independent interleaving of the symbols components. This technique presents good performance assuming the absence of estimation errors for channels characterized by the flat fading. In this article, the performance of that recent technique is analyzed taking into account the effects of channel estimation errors. It is shown, by simulation, that the efficiency of this technique is maintained even under this assumption. Additionally, the impact of the Doppler effect on the system performance is treated and a trade-off between the interleaving depth used and the error probability is achieved.